2011
DOI: 10.1093/intimm/dxr026
|View full text |Cite
|
Sign up to set email alerts
|

Specific expression of PAD4 and citrullinated proteins in lung cancer is not associated with anti-CCP antibody production

Abstract: Anti-citrullinated protein antibodies (ACPAs), produced against citrullinated proteins, are diagnostic and prognostic markers of rheumatoid arthritis (RA). The underlying mechanism that explains the connection of smoking, citrullination [catalyzed by peptidyl arginine deiminases (PADs)] and ACPAs is still unclarified in RA. Thus, we searched for a non-arthritic model in which an increased cell death allows the formation of autoantibodies. Data supporting that lung cancer might be a good candidate are as follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 33 publications
1
23
0
Order By: Relevance
“…All of the protein antigens to which, in their citrullinated forms, the patients in our study had high titre antibodies are present in the lung 25 26. Citrullinated proteins have been identified in lung tissue,11 a finding not exclusive to RA 27. In addition, PAD enzymes, necessary for the conversion of arginine to citrulline in substrate proteins, have also been shown to be present in lung tissue 10 27.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All of the protein antigens to which, in their citrullinated forms, the patients in our study had high titre antibodies are present in the lung 25 26. Citrullinated proteins have been identified in lung tissue,11 a finding not exclusive to RA 27. In addition, PAD enzymes, necessary for the conversion of arginine to citrulline in substrate proteins, have also been shown to be present in lung tissue 10 27.…”
Section: Discussionmentioning
confidence: 99%
“…Citrullinated proteins have been identified in lung tissue,11 a finding not exclusive to RA 27. In addition, PAD enzymes, necessary for the conversion of arginine to citrulline in substrate proteins, have also been shown to be present in lung tissue 10 27. Whether these observations support the possibility of antibody mediated lung tissue damage resulting from a pathogenic interaction between autoantibodies and their cognate citrullinated peptides will require additional mechanistic studies.…”
Section: Discussionmentioning
confidence: 99%
“…Since it is well known that any inflammation can result in the generation of citrullinated peptides [57,60], it may be that the development of citrullinated peptides alone is not enough to trigger an autoimmune response. Such a possibility was proposed in a study by Baka and colleagues who identified lung tissue elevations of citrullinated peptides and PAD-4 in lung tissue from subjects with lung cancer, although few had serum ACPA elevations [61]. These data suggest other factors may be necessary to generate an autoimmune response to citrullinated peptides present in the lung.…”
Section: Mechanisms That May Be Involved In the Generation Of Ra-relamentioning
confidence: 99%
“…In recent years, studies have found that PADI4 is markedly over-expressed in a majority of human cancers, suggesting that PADI4 is a putative target for cancer treatment [9-11]. We recently also reported that the PADI4 gene may be a valid susceptibility gene for oesophageal carcinoma [12].…”
Section: Introductionmentioning
confidence: 99%